2019
DOI: 10.1038/s41379-018-0128-1
|View full text |Cite
|
Sign up to set email alerts
|

VEGFA amplification/increased gene copy number and VEGFA mRNA expression in renal cell carcinoma with TFEB gene alterations

Abstract: Amplification of vascular endothelial growth factor A (VEGFA) has been recently reported in TFEB-amplified renal cell carcinomas regardless the level of TFEB amplification. We sought to determine VEGFA amplification by fluorescent in situ hybridization (FISH) and VEGFA mRNA expression by in situ hybridization (RNAscope 2.5) in a series of 10 renal cell carcinomas with TFEB gene alterations, either amplification and/or rearrangement (t(6;11) renal cell carcinoma). TFEB gene rearrangement was demonstrated in eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 18 publications
(24 reference statements)
3
35
0
Order By: Relevance
“…More recently, renal cell carcinomas with TFEB amplification have been described and appear to be associated with a poor outcome [50,51,52,53,54,55]. TFEB amplification in renal cell carcinoma can occur independently of or in association with TFEB rearrangement [50,55]. TFEB gene rearrangement or amplification increases TFEB expression which causes the subsequent expression of immunohistochemical markers such as cathepsin K, Melan-A, and HMB45 [43].…”
Section: Renal Cell Carcinoma With Tfeb Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, renal cell carcinomas with TFEB amplification have been described and appear to be associated with a poor outcome [50,51,52,53,54,55]. TFEB amplification in renal cell carcinoma can occur independently of or in association with TFEB rearrangement [50,55]. TFEB gene rearrangement or amplification increases TFEB expression which causes the subsequent expression of immunohistochemical markers such as cathepsin K, Melan-A, and HMB45 [43].…”
Section: Renal Cell Carcinoma With Tfeb Amplificationmentioning
confidence: 99%
“…Fourth, TFEB amplified renal cell carcinomas typically have a poor outcome while t(6;11) renal cell carcinomas are usually indolent. Of note, it has been demonstrated that renal cell carcinomas showing TFEB amplification harbor concurrent vascular endothelial growth factor A ( VEGFA ) gene amplification [52,55]. This is may be due to the proximity of those two genes, which are both located on the short arm of chromosome 6.…”
Section: Renal Cell Carcinoma With Tfeb Amplificationmentioning
confidence: 99%
“…The latter subset portends a distinctly worse prognosis, which is likely attributed to increased expression of these spatially peripheral genes. 11,12,28-30,47…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The accruing TFEB -translocated family now also includes COL21A1, CADM2, EWSR1, and CLTC (to name a few). 3,9,11-14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation